Особенности психологического исследования коммуникативной деятельности детей старшего дошкольного возраста с системными нарушениями речи - Мартыненко, И. В.
Theoretic-methodological approaches and methodic of psychological diagnost ics of communicative activity of preschool age children with syst emic © eech disorders are presented in article. The concept of research is based on such psychological principles: syst emic, activity, personal focused and personality-communicative. According to them the © ecial principles of realization of diagnost ics are defi ned as: refl ectivity, integrity of syst em, functional determinancy of communicative activity, its genetic-hierarchical st ructural-andlevel organization, unity of consciousness and activity, etc. The st ages and tasks of experimental invest igation of communicative activity are described.
Keywords: Коммуникативная деятельность